2022
DOI: 10.1101/2022.12.22.22283858
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Methodological approaches to optimize multiplex oral fluid SARS-CoV-2 IgG assay performance and correlation with serologic and neutralizing antibody responses

Abstract: Background. Oral fluid (hereafter, saliva) is a non-invasive and attractive alternative to blood for SARS-CoV-2 IgG testing; however, the heterogeneity of saliva as a matrix poses challenges for immunoassay performance. Objectives. To optimize performance of a magnetic microparticle-based multiplex immunoassay (MIA) for SARS-CoV-2 IgG measurement in saliva, with consideration of: i) threshold setting and validation across different MIA bead batches; ii) sample qualification based on salivary total IgG concentr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…51 In this study, we utilized saliva anti-SCV2 N IgG as a marker for possible prior infection. Saliva anti-SCV2 N IgG has been reported to have a high sensitivity for prior SARS-CoV-2 infections, 49 and we found an 86% sensitivity for known post-vaccine infections in our cohort. Further, we obtained saliva antibody levels at baseline and then regularly (approximately 4 times a year), increasing the likelihood that we would not miss a transient infection-induced increase in saliva anti-SCV2 N antibodies.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…51 In this study, we utilized saliva anti-SCV2 N IgG as a marker for possible prior infection. Saliva anti-SCV2 N IgG has been reported to have a high sensitivity for prior SARS-CoV-2 infections, 49 and we found an 86% sensitivity for known post-vaccine infections in our cohort. Further, we obtained saliva antibody levels at baseline and then regularly (approximately 4 times a year), increasing the likelihood that we would not miss a transient infection-induced increase in saliva anti-SCV2 N antibodies.…”
Section: Discussionsupporting
confidence: 59%
“…47,48 At least 2 studies that found increases in saliva IgA attempted to screen out unrecognized infections by testing for serum anti-SCV2 N IgG. 24,29 While serum anti-SCV2 N is often positive shortly after infection, the sensitivity of anti-SCV2 N IgG for diagnosing prior infection is highly variable (52% -100%) 49,50 and its half-life postinfection is short, with one study estimating it to be only 35 days. 51 In this study, we utilized saliva anti-SCV2 N IgG as a marker for possible prior infection.…”
Section: Discussionmentioning
confidence: 99%
“…Oral fluid samples were separated from device sponges by centrifugation and tested for SARS-CoV-2 nucleocapsid (N), receptor-binding domain (RBD), and spike (S) IgG, using a multiplex bead-based immunoassay based on Luminex technology, which has been described previously 19 , 20 , 52 . Briefly, the multiplex assay included SARS-CoV-2 N, RBD, and S antigens coupled to magnetic microparticles and a background control bead coated with bovine serum albumin (BSA).…”
Section: Methodsmentioning
confidence: 99%
“…However, the invasive process needed for blood collection can limit the use of serological tests. Therefore, introducing saliva samples, composed of both gingival fluid and salivary secretion, can represent huge advantages as saliva collection is easy, non-invasive, and can be self-administrated with a lower risk of contamination (11,12). Regarding daily mucosal antibody production, immunoglobulin A (IgA) production far exceeds the combined production of all other Ig isotypes.…”
Section: Introductionmentioning
confidence: 99%